Economic analysis of participatory forest management in Kenya - Okumu, Boscow (School of Economics, 2018)
The failure of the centralized top down approach to management of common pool resources such as forests led policy makers and donors to conclude that devolution of forest management to local communities can be the only solution to such failures. Developing countries have thus resorted to devolution of forest management to forest adjacent communities through approaches such as joint forest management (JFM) and participatory forest management (PFM). PFM is part of the initiative towards devolution of power of management and decision making from government to local communities. Communities therefore self-organize into community forest associations (CFAs) or forest user groups to manage forest resources. In Kenya for instance, the recent and ongoing forest sector reforms as envisaged in the Forest Act (2005) and the Forest Act (2016) led to devolution of forest management through CFAs and provision of incentives such as plantation establishment and livelihood improvement scheme (PELIS), eco-tourism, harvesting of forest products among others. These efforts were aimed at deepening community participation in forest management and improving welfare of forest adjacent communities. However, despite the numerous efforts aimed at empowering communities to sustainably manage forest resources through PFM and provision of various incentives, the success of PFM in terms of efficiency, equity, accountability and environmental outcomes have been mixed. In this thesis, we contribute empirically to the understanding of how PFM can be successfully implemented and make suggestion for more inclusive, equitable and sustainable forest management in Kenya from a micro perspective using household and community level data collected from 22 CFAs in the Mau forest conservancy. We take into account the values and preferences attached to salient forest ecosystem services by local communities and how this can be used to design incentive schemes like PES to incentivize local communities and also influence devolution of forest management. We also assess the impact of existing incentives specifically PELIS on welfare of forest adjacent communities as well as the environment and the heterogeneous impact of the scheme on household welfare. We then look at the context specific factors influencing the varying levels of success among the CFAs. The thesis therefore, comprises of three separate, but related analysis chapters.